Carotenoid metabolism in mitochondrial function. Issue 3 (13th August 2020) - Lu, Peiran; Wong, Siau Yen; Wu, Lei; Lin, Dingbo
Abstract: Mitochondria are highly dynamic organelles that are found in most eukaryotic organisms. It is broadly accepted that mitochondria originally evolved from prokaryotic bacteria, e.g. proteobacteria. The mitochondrion has its independent genome that encodes 37 genes, including 13 genes for oxidative phosphorylation. Accumulative evidence demonstrates that mitochondria are not only the powerhouse of the cells by supplying adenosine triphosphate, but also exert roles as signalling organelles in the cell fate and function. Numerous factors can affect mitochondria structurally and functionally. Carotenoids are a large group of fat-soluble pigments commonly found in our diets. Recently, much attention has been paid in carotenoids as dietary bioactives in mitochondrial structure and function in human health and disease, though the mechanistic research is limited. Here, we update the recent progress in mitochondrial functioning as signalling organelles in human health and disease, summarize the potential roles of carotenoids in regulation of mitochondrial redox homeostasis, biogenesis, and mitophagy, and discuss the possible approaches for future research in carotenoid regulation of mitochondrial function.